(untitled) (Research, Society and Development, 2020)
Introduction: Hiperdia consists in the registration of patients with Systemic Arterial Hypertension (SAH) and/or Type 2 Diabetes Mellitus (DM) attended by the Unified Health System. Moreover, it is known that the increase in life expectancy and the eating pattern of society contributes to the highlight of these comorbidities. SAH and Type 2 DM are predisposing factors for the emergence of other diseases, which together affect the quality of life of a large part of the socioeconomically vulnerable population. Objectives: To implement the Project in the Condor Family Health Strategy, aiming to reduce the problem of type 2 DM and SAH in the areas covered by the FHS and reduce the incidence through better prevention and health promotion. Methodology: It is a work in which problematization occurs by asking questions to the population about structural problems and recurrent diseases in the Basic Health Unit. Results: The action obtained satisfactory results that met the team’s expectations. In addition, the participants of the action debated and discussed the theme addressed with the team, enabling the exchange of information and knowledge. Final considerations: Technical-scientific knowledge is of paramount importance, however the humanization of the professional must be the majority to understand the various realities and situations arising from the problems of patients in daily life, which was denoted in the methodology applied.